2018
DOI: 10.1155/2018/2651716
|View full text |Cite
|
Sign up to set email alerts
|

Very Rare Liver Neoplasm: Lymphoepithelioma-Like (LEL) Hepatocellular Carcinoma

Abstract: A case of lymphoepithelioma-like (LEL) hepatobiliary carcinoma is reported. To date, only 89 cases of this rare neoplasm have been reported, with both hepatocellular and cholangiocellular histotype. The case reported here could be classified as LEL mixed hepatobiliary carcinoma (Hepato-Cholangio), a histotype not reported so far in the LEL variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The first study [ 50 ] reported a 62-year-old woman who was admitted to the hospital because of right upper abdominal drop pain with hepatitis B. Laboratory examination showed that AFP was 394.90 ng/ml (0–7 ng/ml).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first study [ 50 ] reported a 62-year-old woman who was admitted to the hospital because of right upper abdominal drop pain with hepatitis B. Laboratory examination showed that AFP was 394.90 ng/ml (0–7 ng/ml).…”
Section: Discussionmentioning
confidence: 99%
“…of lesions Size, mm Treatment FU, mo. Outcome Immunohistochemical markers AFP Hepatocyte CK7 CK19 CK18 EBER First case M 62 Asian + + 1 28 LR 13 AWOD + + + + Filotico et al [ 50 ] F 62 NA + + 1 50 LR NA NA + + + + NA NA Wei et al [ 51 ] M 40 Asian + + 1 21 LR 30 AWOD + + + + F female, M male, + positive, − negative, HBV hepatitis B virus, HCV hepatitis C virus, NA not available, No . number, AFP a-fetoprotein, AWOD alive without disease, FU follow-up, mo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first literature [50] reported a 62 years old woman who was admitted to the hospital because of the right upper abdominal drop pain with hepatitis B.Laboratory examination showed that AFP:…”
Section: Discussionmentioning
confidence: 99%
“…In the future, more research and reports are needed to improve this special pathological type. [19,23,50] . Because of its nonspecific clinical manifestations, it is difficult to diagnose LELC before operation.…”
Section: Discussionmentioning
confidence: 99%